Il trilinguismo delle lettere «italiane» - MARTI, Mario (Giornale storico della letteratura italiana, 2011)
Abstract This article retraces the period that marked the appearance of the first examples of the vernacular and subsequently of its literature. The latter did not remain isolated but continued to find expression in Latin and in the various local vernaculars, which later on, with the codification of a national language, became dialects. There emerges from this study a general picture of how Italian literature has evolved and how, in its various forms, it has provided the nation with a cultural identity.